2018
DOI: 10.1002/uog.18823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gestational diabetes on fetal autonomic nervous system: a study using phase‐rectified signal‐averaging analysis

Abstract: Our findings show increased ANS activity in fetuses of diabetic mothers in late gestation. Analysis of human fetal cardiovascular and ANS function by PRSA may offer improved surveillance over conventional techniques linking GDM pregnancy to future cardiovascular dysfunction in the offspring. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The result furtherly proved the potentially significant effect hyperglycemia has on the vascular wall, even over a short duration in pregnancy. The hyperglycemia state not only affect maternal hemodynamics during pregnancy, but also affect the developing cardiovascular system and autonomic nervous system in the fetus [21,22]. The predictive value of maternal RHR we found in the current study is similar with the finding of Sirico et al [8], whose research found that early pregnancy fetal heart rate could be an independently correlated to the risk of developing GDM and a threshold of 162 bpm has high detection rate for GDM.…”
Section: Discussionsupporting
confidence: 90%
“…The result furtherly proved the potentially significant effect hyperglycemia has on the vascular wall, even over a short duration in pregnancy. The hyperglycemia state not only affect maternal hemodynamics during pregnancy, but also affect the developing cardiovascular system and autonomic nervous system in the fetus [21,22]. The predictive value of maternal RHR we found in the current study is similar with the finding of Sirico et al [8], whose research found that early pregnancy fetal heart rate could be an independently correlated to the risk of developing GDM and a threshold of 162 bpm has high detection rate for GDM.…”
Section: Discussionsupporting
confidence: 90%
“…The average deceleration capacity (ADC) and acceleration capacity (AAC) of heart rate indices were established and assessed as indicators of these complex regulations reflecting the autonomic nervous system (ANS) function, in adults and the fetuses. Indeed, our study group already showed that fetal ANS is affected by maternal GDM [9].…”
Section: Introductionmentioning
confidence: 68%
“…This is in contrast to control fetuses who showed a continuous rise in HRV over this time (Fehlert et al, 2017). However, another study (Lobmaier et al, 2018) showed evidence of increased autonomic activity, as measured by AC and DC in fetal heart rate on cardiotocography at rest in late gestation in fetuses of mothers with GDM compared to controls. Clearly, further studies are needed to advance understanding of autonomic maturation in the fetus developing in a GDM environment.…”
Section: Diabetes In Pregnancymentioning
confidence: 81%